THU0510 Hypersensitivity, alexithymia and disease characteristics of patients presenting with symptoms of fibromyalgia. (12th June 2018) - Jacobs, H.; Grillet, B.A.; De Bacquer, D.
Abstract : Background: Fibromyalgia (FM) is characterised by chronic widespread pain and other symptoms such as fatigue, sleep disturbances and cognitive problems. Psychosocial factors and personality traits may be present in a variable degree and may play a role in the perception, coping and treatment of FM. Objectives: We looked for symptoms of hyperventilation, depression, anxiety and burn-out as well as for personality traits such as hypersensitivity and alexithymia in a large sample of patients. We looked at differences in prevalence of these symptoms in the population when selected by the 1990 FM classification criteria and by the 2010 diagnostic FM criteria. Methods: A large group of patients presenting on the Unit of Physical Medicine between 2014 and 2017 with chronic widespread pain was analysed and grouped depending on the 1990 ACR classification criteria for FM on one hand and the 2010 ACR diagnostic criteria for FM on the other hand. Self-administered tools used were the Nijmegen questionnaire (hyperventilation), the Aron questionnaire (hypersensitivity), the HADS questionnaire (anxiety and depression), the BMS-10 questionnaire (burn-out) and the TAS alexithymia questionnaire. Results: Out of 1085 patients, 828 (76%) fulfilled the 1990 ACR classification criteria for FM. Hyperventilation (score ≥12) was found in 97% and hypersensitivity (score ≥12) in 75%. Symptoms of anxiety and depression (scores≥11) were observed in 59% and 36% respectively. Burn-out (score ≥4.5) was seen in 40% of patients while a high TAS score (≥8) was found in 70% of patients. Overall, 906 patients fulfilled the 2010 ACR diagnostic criteria for FM. The distributions of disease characteristics and personality traits in this population were very similar. Only 38 out of these 906 patients had a wide spread pain index (WPI) of 3 to 6. Conclusions: A significant number of patients demonstrated high levels of anxiety, more than depression. Hypersensitivity and alexithymia were also found to be highly prevalent. There was a substantial level of hyperventilation. It may be useful to consider all these characteristics in the development of treatment programs for FM patients. Results were similar when groups were selected by 1990 ACR classification criteria for FM or by the 2010 ACR diagnostic criteria for FM. Only a minority of patients had a WPI of 3 to 6. References: [1] Van Dixhoorn J, et al. 1985. [2] Wolfe, et al. 1990. [3] Aron, et al. 1997. [4] Maslach, et al. 1996. [5] Wolfe, et al. 2010. [6] Maes, et al. 2014. Disclosure of Interest: None declared